2018
DOI: 10.1111/jora.12406
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Links Among Shyness, Peer Relations, and Internalizing Problems in Chinese Young Adolescents

Abstract: This study evaluates a model linking shyness, aspects of peer relations, and internalizing problems among young adolescents in the People's Republic of China. Participants were 547 young adolescents from Shanghai, China (46% boys; M = 10.35 years, SD = 0.77 years) who completed peer nominations of shyness, rejection, and victimization, and self-report measures of loneliness, depression, and friendship support. Analyses demonstrated that peer difficulties (rejection, victimization) mediated the associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 64 publications
3
29
0
1
Order By: Relevance
“…Researchers have discussed ways in which culture may affect shy children’s adjustment. For example, they have proposed that culture in the microsystem affects shy children’s adjustment through social evaluations from other people and negative relationships with peers and teachers (Chen, ; Coplan, Liu, Cao, Chen, & Li, ; Liu, Bowker, et al, ). In addition, although not focused on shy children’s adjustment, recent work points to the importance of culture at the person level (i.e., children’s own cultural values).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have discussed ways in which culture may affect shy children’s adjustment. For example, they have proposed that culture in the microsystem affects shy children’s adjustment through social evaluations from other people and negative relationships with peers and teachers (Chen, ; Coplan, Liu, Cao, Chen, & Li, ; Liu, Bowker, et al, ). In addition, although not focused on shy children’s adjustment, recent work points to the importance of culture at the person level (i.e., children’s own cultural values).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although not focused on shy children’s adjustment, recent work points to the importance of culture at the person level (i.e., children’s own cultural values). Liu, Fu and colleagues () found that Chinese children’s own self‐ and group‐orientations were associated with adjustment in both rural and urban contexts, but self‐orientations were associated with more positive outcomes in the urban sample, and group‐orientations were associated with more positive outcomes in the rural sample; thus, cultural orientations at both the person level and the context level may play a role in Chinese children’s adjustment. In a U.S. Latino sample, Schneider and Gudiño () found that the association between earlier behavioral inhibition and later PTSD symptoms after exposure to community violence was stronger for children with high collectivistic (Latino) values; these results suggest that collectivistic values influenced the way inhibited children viewed their traumatic experience and coped.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this study, we explored whether unsociability would be more negatively associated with peer relations in boys than in girls. Moreover, previous studies did not reveal any gender differences in the relations between peer problems and child psychological maladjustment in Chinese culture (e.g., Liu et al, 2019).…”
Section: Unsociability Peer Relations and Adjustment: Moderating mentioning
confidence: 76%
“…Indeed, results from several studies suggest that unsociability is largely unassociated with indices of psychological maladjustment, particularly among younger children (for a recent review, see Coplan et al, 2018). For example, Coplan et al (2019) found that in Canada, kindergarten child unsociability was not associated with peer problems, social anxiety, or depression. Similarly, Sette, Zava, Baumgartner, Baiocco, and Coplan (2017) reported that unsociability only related to child's reported preference for solitary activities, but not related to other internalizing problems among Italian preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Utangaçlığın önemli belirleyicilerinden birisi de toplumsal değer ve normlardan etkilenmesiyle ilgilidir. Nitekim kimi araştırmacılar utangaçlığı toplumun temel değerlerinden güç alarak yaratılan ve yaşanış sıklığında kültürel yapının belirleyici rol oynadığı bir duygu olarak tanımlamaktadırlar (Chen, 2018;Liu, Bowker, Coplan, Yang, Li, & Chen, 2018;Zimbardo, 1979). Bu bakımdan utangaçlığın gelişiminde kişisel deneyimlerin yanısıra kültürel faktörlerin önemli rolü bulunmakta (Chen & Schmidt, 2015) buna paralel olarak da utangaçlık genel bir inanış ve bakış açısıyla kadınlara özgü bir özellik olarak görülmektedir (Shields, 2005).…”
Section: Introductionunclassified